Human cytomegalovirus overcomes SAMHD1 restriction in macrophages via pUL97 - Businger, Ramona; Deutschmann, Janina; Gruska, Iris; Milbradt, Jens; Wiebusch, Lüder; Gramberg, Thomas; Schindler, Michael (Nature Microbiology, 2019)
The host restriction factor sterile alpha motif and histidine–aspartate domain-containing protein 1 (SAMHD1) is an important component of the innate immune system. By regulating the intracellular nucleotide pool, SAMHD1 influences cell division and restricts the replication of viruses that depend on high nucleotide concentrations. Human cytomegalovirus (HCMV) is a pathogenic virus with a tropism for non-dividing myeloid cells, in which SAMHD1 is catalytically active. Here we investigate how HCMV achieves efficient propagation in these cells despite the SAMHD1-mediated dNTP depletion. Our analysis reveals that SAMHD1 has the capability to suppress HCMV replication. However, HCMV has evolved potent countermeasures to circumvent this block. HCMV interferes with SAMHD1 steady-state expression and actively induces SAMHD1 phosphorylation using the viral kinase pUL97 and by hijacking cellular kinases. These actions convert SAMHD1 to its inactive phosphorylated form. This mechanism of SAMHD1 inactivation by phosphorylation might also be used by other viruses to overcome intrinsic immunity.
CRIS-Team Scopus Importer:2019-11-01